Analysis of Partial Discharge Due to Movement of Spherical Particle in Power Transformer Using Computational Fluid Dynamics - Vasantha Gowri, N; Ramalinga Raju, M; P.Singh, B (International Journal of Engineering and Technology, 2018)
Power transformer is costly and very important equipment in power sector. Failure of power transformer causes colossal damage to the power system. One of the important reasons for transformer failure is event of Partial Discharge (PD) in the transformer. Numbers of non-conducting and conducting particle are available in the transformer. Conducting particles available in the transformer or mineral oil entering into winding space, strike the energized winding of the transformer cause PD to occur. Movement pattern of particle administrates the probability of particle striking the winding. Analysis of movement of particles proximate to HV winding helps in understanding the occurrence of PD. This paper deals with tracking of aluminum and copper particles of various sizes available inside the transformer.Â